Video-based behavioral change communication to change consumption patterns: Experimental evidence from urban Ethiopia - Abate, Gashaw T.; Baye, Kaleab; de Brauw, Alan; Hirvonen, Kalle; Wolle, Abdulazize (International Food Policy Research Institute, 2021)
Poor diet quality has been widely identified as a primary reason for malnutrition and the increasing burden of non-communicable diseases in low- and middle-income countries. Low consumption of fruits and vegetables contributes to poor diet quality, and one factor leading to low fruit and vegetable consumption is limited consumer awareness of the health and nutrition benefits of consumption. In this study, we experimentally assess a method of increasing consumer awareness, specifically, through showing households two different versions of a video embedded with messages about increasing fruit and vegetable consumption. The first video included just the basic recommended consumption behavior messages, while the second video also explained why and how fruit and vegetable consumption could improve health and nutrition outcomes. Even four months after viewing the video, average household consumption of fruits and vegetables increased by about 10 percent in both treatment groups relative to the control group, both in kilocalorie and consumption expenditure terms. The videos were developed to eventually show on national TV, suggesting that embedding dietary BCC messages in popular media can have positive impacts on diet quality at scale.